Foundations of education : a Christian vision - Etherington, Matthew (Eugene, Oregon : Wipf & Stock Publishers, 2014)
Ideas about education have consequences. This book, edited by Matthew Etherington, provides readers with ideas and insights drawn from fifteen international scholars in Christian thought within the fields of philosophy, theology, and education. Each author responds to the philosophical, historical, and sociological challenges that confront their particular line of educational inquiry. The authors offer a view of Christian education that promotes truth, human dignity, peace, love, diversity, and justice. The book critically analyzes public discourse on education, including the wisdom, actions, recommendations, and controversies of Christian education in the twenty-first century. This timely book will appeal to those concerned with Christian perspectives on education, Aboriginality, gender, history, evangelism, secularism, constructivism, purpose, hope, school choice, and community.
Includes bibliographical references.
Print version record.
Keywords: Education -- Religious aspects -- Christianity; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books